2017
DOI: 10.3390/ijtpp3010002
|View full text |Cite
|
Sign up to set email alerts
|

Flow Control Methods and Their Applicability in Low-Reynolds-Number Centrifugal Compressors—A Review

Abstract: Abstract:The decrease in the performance of centrifugal compressors operating at low Reynolds numbers (e.g., unmanned aerial vehicles at high altitudes or small turbomachines) can reach 10% due to increased friction. The purposes of this review are to represent the state-of-the-art of the active and passive flow control methods used to improve performance and/or widen the operating range in numerous engineering applications, and to investigate their applicability in low-Reynolds-number centrifugal compressors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 207 publications
(299 reference statements)
1
5
0
Order By: Relevance
“…Apart from the aforementioned multielement aerofoils, there are several other multielement aerofoils that have been used on aircraft wings or HAWTs, but still have not been implemented on VAWTs, for example, four-element F I G U R E 8 Several potential dynamics stall control devices for LVAWTs, (a) types of riblet shapes (Tiainen et al, 2018), (b) illustration of aerofoil with flow vane (Pechlivanoglou, 2013), and (c) four-element aerofoil of DU 00-W-401 (Ragheb & Selig, 2011) T A B L E 3 Summary of PFCDs that have a potential to be integrated to LVAWTs . By comparing the lift-to-drag ratio, the results showed that four-element aerofoils with one main part, two flap parts, and one sturt part (see Figure 8c) produced the maximum lift-to-drag ratio, compared with the other designs.…”
Section: Four-element Aerofoilmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the aforementioned multielement aerofoils, there are several other multielement aerofoils that have been used on aircraft wings or HAWTs, but still have not been implemented on VAWTs, for example, four-element F I G U R E 8 Several potential dynamics stall control devices for LVAWTs, (a) types of riblet shapes (Tiainen et al, 2018), (b) illustration of aerofoil with flow vane (Pechlivanoglou, 2013), and (c) four-element aerofoil of DU 00-W-401 (Ragheb & Selig, 2011) T A B L E 3 Summary of PFCDs that have a potential to be integrated to LVAWTs . By comparing the lift-to-drag ratio, the results showed that four-element aerofoils with one main part, two flap parts, and one sturt part (see Figure 8c) produced the maximum lift-to-drag ratio, compared with the other designs.…”
Section: Four-element Aerofoilmentioning
confidence: 99%
“…Several potential dynamics stall control devices for LVAWTs, (a) types of riblet shapes (Tiainen et al, 2018), (b) illustration of aerofoil with flow vane (Pechlivanoglou, 2013), and (c) four‐element aerofoil of DU 00‐W‐401 (Ragheb & Selig, 2011)…”
Section: Potential Pfcds For Lvawtsmentioning
confidence: 99%
“…Both active and passive flow controls have their own advantages and disadvantages based on their applications. For example, a passive flow control does not need a power input whereas active flow control needs a power to actuate a moving attachment [5]. Furthermore, in active flow control the parameter which controls the flow can be varied according to the flow field as desired.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is accompanied by thickening of the boundary layer and increased pressure drag, and successful application to curved surfaces remains to be shown. Another example of practical applications is provided by Tiainen et al, 19 where the focus is on both active and passive BLC in centrifugal compressors at low-Reynolds-numbers. Possible benefits for unmanned air vehicles (UAVs) and small turbomachines include reducing drag, increasing blade loading, or reducing tip leakage.…”
Section: Background and Introductionmentioning
confidence: 99%